Effects of Bauxite and Alumina Exposure on Incidence of Cancer - Meta-analysis - Thevi, T.; Abas, A. L. (Kathmandu University Medical Journal, 2020)
Bauxite is an ore from which Aluminium is produced. Malaysia, once the leading producer of bauxite has reduced production as mining activity has caused community outrage. Due to concerns about health concerns, rising pollution and environmental hazards, the government has revoked the licenses of bauxite miners. We therefore did a meta-analysis to assess the relationship between exposure to Bauxite and Alumina with incidence of various types of cancers. Bauxite mines and alumina refineries. Individuals of all ages exposed to Bauxite and Alumina. Exposure to bauxite and alumina. Incidence due to overall cancers and specific types of cancers. Exposure to bauxite and alumina did not cause variations in incidence of overall cancer and specific types of cancer such as cancer of lip, cancer of the oral cavity and pharynx, cancer of digestive organs and others. We conclude that there is no evidence that bauxite or alumina exposure cause increase incidence of cancer but due to the small number of studies included in this review, we recommend more cohort studies to be done in future.